Rare forms of cerebral amyloid angiopathy: pathogenesis, biological and clinical features of CAA-ri and iCAA - Storti, Benedetta; Gabriel, Maria Magdalena; Sennfält, Stefan; Canavero, Isabella; Rifino, Nicola; Gatti, Laura; Bersano, Anna (Frontiers in Neuroscience, 2023)
Thanks to a more widespread knowledge of the disease, and improved diagnostic techniques, the clinical spectrum of cerebral amyloid angiopathy (CAA) is now broad. Sporadic CAA, hereditary CAA, CAA-related inflammation (CAA-ri) and iatrogenic CAA (iCAA) create a clinical and radiological continuum which is intriguing and only partially discovered. Despite being relatively rare, CAA-ri, an aggressive subtype of CAA with vascular inflammation, has gained growing attention also because of the therapeutic efficacy of anti-inflammatory and immunomodulating drugs. More recently, diagnostic criteria have been proposed for an unusual variant of CAA, probably related to an iatrogenic origin (iCAA), toward which there is mounting scientific interest. These atypical forms of CAA are still poorly known, and their recognition can be challenging and deserve to be pursued in specialized referral centres. The aim of this brief review is to focus current developments in the field of rare forms of CAA, its pathogenesis as well as clinical and biological features in order to increase awareness of these rare forms.